A novel of PEG-conjugated phthalocyanine and evaluation of its photocytotoxicity and antibacterial properties for photodynamic therapy - Durmuş İşleyen, Naciye; Öztürk, Yetkin; Turanlı Yıldız, Burcu; Çakar, Zeynep Petek; Göksel Şahin, Meltem; Durmuş, Mahmut; Hepüzer Gürsel, Yeşim; Sesalan, Behice Şebnem; YİĞİT, CANAN USLAN (World Sci Publ Co Inc, 27 Warren St, Ste 401-402, Hackensack, Nj 07601 USA, 2018)
A poly(ethylene glycol) (PEG)-conjugated silicon(IV) phthalocyanine axially substituted with (PEG1000) chains (SiPc-PEG) was synthesized, and this novel phthalocyanine was characterized by H-1-NMR, FT-IR and UV-Vis spectrophotometric methods. Elemental analysis data were beneficial for the evaluation of the chemical structure of the new compound. The total number of (O-CH2-CH2 units was calculated as 44 and the structure of the new PEG-conjugated silicon phthalocyanine was determined by the use of integral areas in H-1-NMR spectrum and the ratio of SiPc: PEG1000 was found as 1:2. The photophysical and photochemical properties were determined in both DMSO and aqueous solutions. In addition, the photocytotoxicity of the novel PEG-conjugated silicon(IV) phthalocyanine was also examined by testing against human cervical-carcinoma (HeLa) and hepato-carcinoma cells (HuH-7). The IC50 value for the SiPc-PEG compound was determined as 0.28 mu M for HeLa cells and 0.4 mu M for HuH-7 cells. These results imply that HeLa cells are apparently more responsive to photodynamic therapy (PDT) treatment by SiPc-PEG than HuH-7 cells at low concentrations (up to 0.5 mu M) of the studied photosensitizer. Additionally, SiPc-PEG showed antibacterial activity against Escherichia coli at 48 h of incubation, the viabilities of E. coli cultures exposed to 1000 mu g/mL and 2500 mu g/mL SiPc-PEG concentration were reduced by about 90%, and the additional growth inhibitory effect of photoactivation was also observed clearly at these efficient concentrations. To conclude, the novel compound may have a high potential for photodynamic therapy.
Keywords: PEG-conjugated silicon phthalocyanine; antibacterial effect; photocytotoxicity; antitumoral activity; photodynamic therapy; Halogenated Silicon(Iv) Phthalocyanines; Poly(Ethylene Glycol) Chains; Bovine Serum-Albumin; Biological-Properties; Hela-Cells; Photochemical Properties; Zinc Phthalocyanines; Photophysical Properties; Metal Phthalocyanines; Photosensitizers